Suprachoroidal injection of triamcinolone acetonide for management of resistant diabetic macular edema (SCTA): original article - Ateeq, Asim; Saima Majid; Nasir Ahmed Memon; Nausheen Hayat; Abdul Qadeem Somroo; Abdul Fattah Memon (Journal of the Pakistan Medical Association, 2023)
Objective: To estimate the effects and safety of suprachoroidal triamcinolone acetonide injections in treating patients with resistant diabetic macular oedema. Methods: The quasi-experimental study was conducted at the Isra Postgraduate Institute of Ophthalmology, Al-Ibrahim Eye Hospital, Karachi, from November 2019 to March 2020, and adult patients of either gender with uncontrolled diabetes mellitus. Central macular thickness, intraocular pressure and best corrected visual acuity were recorded at baseline, and the patients were followed up at one and three months after the suprachoroidal triamcinolone acetonide injection and post-intervention parameters were compared. Data was analysed using SPSS 20. Results: There were 60 patients with a mean age of 49.25+/-5.6 years. Of the 70 eyes, 38(54.30%) belonged to male subjects and 32(45.70%) to female subjects. There were significant differences in terms of central macular thickness and the best corrected visual acuity at both follow-ups compared to the baseline readings (p<0.05). Conclusion: Suprachoroidal triamcinolone acetonide injection significantly reduced diabetic macular oedema. Key Words: Diabetic macular oedema, Intravitreal, Suprachoroidal, Triamcinolone.